Effect of Pebax coating on gas separation properties of rGO-ZIF-8 pes mixed matrix membranes: article / Haldizam Saidi ... [et al.] - Saidi, Haldizam; Alias, Nur Hashimah; Shahruddin, Munawar Zaman; Othman, Nur Hidayati (2019)
Mixed matrix membranes (MMMs) attract great attention due to their outstanding gas separation performance. The compatibility between the fillers and the polymer matrix is one of the key points for the preparation of high-performance MMM. In this study, MMMs consisting of 10 wt% in-situ synthesized rGO/ZIF-8 hybrid nanofillers were fabricated for gas separation. Pebax-1657 at 2, 3 and 4 wt% concentration was added as coating layer to study the effect of different concentration pebax on the permeability and selectivity of rGO-ZIF-8 PES MMMs. The pebax solution was prepared by dissolving it in a dilute ethyl alcohol in ratio of 70:30. The operating pressure of gas permeation varied from 1 bar to 5 bar. It was found that the permeation rate increase with higher pressure and decrease with increase coating time and concentration of pebax. Based on the result of 3%PEBAX/rGO-ZIF-8 PES MMMs, permeability of CO2, CH4, N2, and O2 gas shows 19%, 93% 86% and 79% decrease, in permeation rate for each gas respectively and the selectivity increase from 1.76 to 10.19 when compare to 3%PEBAX/PES. The XRD, FTIR TGA and BET analysis was done for the synthesized nanofillers and fabricated PES MMMs membrane of coated and uncoated. The 3%PEBAX/rGO-ZIF-8 PES gave the highest selectivity of 10.19, 3 bar with CO2 and N2 permeance of 79.68 and 7.82 barrer respectively whereas for CO2 no gas flow was recorded during the test.